Division of roles and endogenous specialization. (22nd December 2019) - Christensen, Michael; Knudsen, Thorbjørn
Abstract: We extend a core idea in James G. March's work, that an ecology of experiential learners may generate endogenous specialization. Although prior work has studied how division of labor, in the form of task assignments, drives experience effects, we are interested in understanding how division of roles endogenously drives a process of task division, which in turn drives experience effects. The insights from a case study in a bank allow us to capture joint learning among employees who screen loan applications. Organizational roles provide constraints on the way learners interact, and thereby shape the pattern of the learning process as reflected in the subjects' screening functions. We develop an analytical platform—a dynamic screening model—that allow us to extract a mechanism, which can explain the observed screening functions. After fitting the model to data obtained from the case study, we find that organizations' role structures generate distinct patterns of interaction, which in turn lead to distinct patterns of specialization among agents. Our analytical platform offers a broad range of extensions that can be applied to study organizational design and learning. More generally, we hope to revitalize the notion of the organization as a system of interacting roles as a useful analytical perspective in strategy and organization science.